Deep Seabed Mining And Precautionary Pause: Possibility And Legal Challenges - Ariningtyas, Agnes; Indriyani, Rachma; Adiastuti, Anugrah (WARKAT, 2024)
Critical minerals that are greatly needed for green technology could be found in potentially promising quantities on the seafloor. Nevertheless, there are long-term environmental effects associated with recovering such resources. This research argues based on international law of the sea which applies normative-legal research method using statutory and conceptual approaches. The main findings of this research reveal that the proponents argue that extracting minerals from the deep sea could be beneficial for the humankind. However, many nations are pushing for a ban or delay on seabed mining due to a lack of international law and knowledge of the full environmental effects. It is unclear if the International Seabed Authority (ISA) will approve such a ban, but some scientists believe mining will soon start. Therefore, precautionary approach needs to be implemented to minimize the potential destructive impacts due to the deep seabed mining (DSM) activities.